The Fate of Tuberculosis Cases After Two Years of Dots Chemotherapy in Aurangabad City, Maharashtra - Rahul H Dandekar; Jagannath V Dixit (Medsci Publications, 2014)
Background: Majority of relapses after Short Course of Chemotherapy (SCC) occur within two years after treatment initiation. Change in disease status over a period of time is termed as fate. During a non-intervention period, the fate of cases reflects the natural dynamics of the disease and to study this will likely provides an insight into the effectiveness of the control programme. Objectives: The objective of this study was to assess the fate of TB cases after two years of Directly Observed Treatment Short Course Chemotherapy (DOTS). Methodology: The present cross section study was carried out on TB cases which were registered for DOTS in 2006. The cases were distributed into various strata by Stratified Random Sampling method and to get the representation of each type of TB cases, cases were chosen by Systematic Random Sampling Method from each stratum. Out of 357, total 304 cases were contacted. Results: Out of total 304, 254(83.55%) cases had favourable fate and 50(16.45%) unfavourable. Of 40 died cases, 12(30%) cases had died during DOTS and 28(70%) died within two years after completion of DOTS treatment. After two years of DOTS Chemotherapy, four cases found bacteriologically sputum positive and six previously sputum negative and extra-pulmonary cases had relapsed with clinical and histological evidence of current active TB. But primary outcome of four bacteriologically positive sputum cases was that two cases had cured, one TC and one defaulted. Thus the relapse rate was 0.99% (3/304). Total 8 (29.63%) cases were found on retreatment at the time of interview. Conclusion: This study may add the knowledge on TB, time trend of mortality and natural dynamic of TB disease.